Transcranial Magnetic stimulation in Neurodegenerative Diseases: Basics and Clinical Applications - Burak Yuluğ; Ahmet Aslan (Acta Medica Alanya)
Transcranial Magnetic Stimulation (rTMS) non-invasively modulates brain networks via stimulating relevant brain regions responsible for motor and cognitive functions. However, replicating human and animal data suggests the therapeutic role of repetitive transcranial magnetic stimulation (rTMS) in many neurological diseases. In this letter, we evaluate the role of rTMS on the network neuroplasticity and neuroprotective pathways, including especially the Brain-Derived Neurotrophic Factor (BDNF), which mediates the pro-cognitive and neuroprotective effects of rTMs, suggesting that rTMS is a potential neuroprotective and pro-cognitive therapy.